A pragmatic lab-based tool for risk assessment in cardiac critical care: data from the Critical Care Cardiology Trials Network (CCCTN) Registry. Issue 3 (3rd February 2022) - Patel, Siddharth M; Jentzer, Jacob C; Alviar, Carlos L; Baird-Zars, Vivian M; Barsness, Gregory W; Berg, David D; Bohula, Erin A; Daniels, Lori B; DeFilippis, Andrew P; Keeley, Ellen C; Kontos, Michael C; Lawler, Patrick R; et al.
Abstract: Aims: Contemporary cardiac intensive care unit (CICU) outcomes remain highly heterogeneous. As such, a risk-stratification tool using readily available lab data at time of CICU admission may help inform clinical decision-making. Methods and results: The primary derivation cohort included 4352 consecutive CICU admissions across 25 tertiary care CICUs included in the Critical Care Cardiology Trials Network (CCCTN) Registry. Candidate lab indicators were assessed using multivariable logistic regression. An integer risk score incorporating the top independent lab indicators associated with in-hospital mortality was developed. External validation was performed in a separate CICU cohort of 9716 patients from the Mayo Clinic (Rochester, MN, USA). On multivariable analysis, lower pH [odds ratio (OR) 1.96, 95% confidence interval (CI) 1.72–2.24], higher lactate (OR 1.40, 95% CI 1.22–1.62), lower estimated glomerular filtration rate (OR 1.26, 95% CI 1.10–1.45), and lower platelets (OR 1.18, 95% CI 1.05–1.32) were the top four independent lab indicators associated with higher in-hospital mortality. Incorporated into the CCCTN Lab-Based Risk Score, these four lab indicators identified a 20-fold gradient in mortality risk with very good discrimination (C-index 0.82, 95% CI 0.80–0.84) in the derivation cohort. Validation of the risk score in a separate cohort of 3888 patients from the Registry demonstrated good performance (C-index of 0.82; 95% CI 0.80–0.84). Performance remained consistent in the external validation cohort (C-index 0.79, 95% CI 0.77–0.80). Calibration was very good in both validation cohorts ( r = 0.99). Conclusion: A simple integer risk score utilizing readily available lab indicators at time of CICU admission may accurately stratify in-hospital mortality risk.